Mining spillovers and the formal-informal duality in manufacturing and services - Saumik Paul; Dhushyanth Raju (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
This study examines the effects of mining productivity shocks on the formal-informal duality in manufacturing and services. Using firm census data from 2014 for Ghana, we measure the rates of informality along extensive (unregistered firms) and intensive (registered firms hiring labourers 'off the books') margins. We find that the changes in the rates of informality along both margins across sectors following mining shocks are heterogeneous. We also find that the lack of duality between informal and formal firms across the development phases of mining is driven by increasing heterogeneity in productivity and skilled employment within informal and formal firms, and less by the incidence of firms sorting into the formal and informal sectors. The lack of duality was most noticeable among heavy manufacturing firms established after the start of oil and gas production in 2010, driven by more-productive newly established unregistered firms with lower labour and energy cost shares than newly established registered firms.
Keywords: D22; E26; J46; L14; 330; mining; informality; firm productivity; Ghana